2008
DOI: 10.1007/s00535-008-2269-3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of living-donor liver transplantation on esophageal varices

Abstract: LDLT results in improvement of EVs. EVs improved in 86% of the patients. Measurement of RRGV with MDCT is a good tool for prediction of EV improvement after LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has already been reported that bleeding esophagogastric varices caused by portal hypertension improve after liver transplantation [1,2,3]. However, compared with full-size liver transplantation, a higher risk of re-bleeding has been observed after partial liver transplantation such as living donor liver transplantation (LDLT) [4,5].…”
mentioning
confidence: 99%
“…It has already been reported that bleeding esophagogastric varices caused by portal hypertension improve after liver transplantation [1,2,3]. However, compared with full-size liver transplantation, a higher risk of re-bleeding has been observed after partial liver transplantation such as living donor liver transplantation (LDLT) [4,5].…”
mentioning
confidence: 99%